Construction of obsidian during explosive-effusive eruptions: insights from microlite crystals in obsidian pyroclasts - Aubin, Wade L.; Gardner, James E.; Watkins, James M.; Lloyd, Madeline H. (Frontiers in Earth Science, 2023)
Obsidian pyroclasts are common in deposits from silicic sub-Plinian eruptions and can record pre- and syn-eruptive processes in the volcanic conduit. Previous work focusing on dissolved volatiles and vesicle textures has been useful in extracting timescales of sintering, diffusion, and vesicle relaxation recorded by obsidian pyroclasts. Here we focus on microlite crystals (<100 µm in size) to augment previous work because they form at different rates than vesicles or than rates of volatile degassing. Hence, they have the potential to disclose additional information about processes occurring in an explosive conduit. We examine microlites in 72 samples from tephra deposits of the 1340 C.E. North Mono eruption, California, U.S.A., and complement these measurements with hydrothermal experiments at 800°C, 10–50 MPa, and durations from 1 to 7 h. Three observations of the natural obsidians further elucidate their formation. First, microlite number densities (MND) increased as the eruption progressed. Second, multiple microlite morphologies occur for feldspars (blocky, swallowtail, tabular, cluster, skeletal) and pyroxenes (individual rods or clusters of acicular crystals) in each obsidian, regardless of any other characteristic. Third, microlite orientations correlate with the dominant morphology of vesicles, being generally well aligned in samples with ellipsoid vesicles, generally poorly aligned in samples with spherical vesicles, and either unaligned or aligned into planes in samples with distorted vesicles. In hydrothermal experiments, MND increase with time, microlites display only one morphology, and microlites are randomly oriented at any given pressure or temperature. When compared to natural obsidians, our experiments suggest most of the microlites could have grown in ≤∼7 h. The variety of microlite morphologies and orientations argue for repeated in-conduit fragmentation and sintering, consistent with the idea that each individual obsidian pyroclast is the product of ash sintering at multiple depths in the conduit prior to finally being erupted. During most of the eruption, obsidian pyroclasts were extracted from many depths in the conduit, preserving an array of volatile contents and microlite textures. Near the end of the explosive phase, however, higher MND record longer periods of stalling while dissolved volatile contents record vapor-melt equilibration at shallow depths in the conduit.